Migración del hardware proyecto Oberon 2013 de Spartan 3 a Spartan 3E (2018)
Oberon Project 2013 is the building a computer system from hardware to applications which was implemented in FPGA a Spartan 3, this FPGA went out of production while other FPGA enter the market. Those FPGA have similar features. To keep the project it is necessary to migrate to other hardware. In this case, we chose FPGA Spartan 3E because this FPGA have similar features, except the memory. The Spartan 3 memory uses direct addressing while the Spartan 3E memory uses indirect addressing and need an auto-refresh circuit. For this reason, we had to create an arbitration circuit so the computer saw new system memory as it were the old memory.